2009
DOI: 10.1002/humu.20948
|View full text |Cite
|
Sign up to set email alerts
|

Alu-Alurecombination underlies the vast majority of largeVHLgermline deletions: Molecular characterization and genotype-phenotype correlations in VHL patients

Abstract: Von Hippel-Lindau disease (VHL) is an autosomal dominant cancer syndrome. Affected individuals are predisposed to multiple tumors, primarily of the central nervous system (CNS), eyes, adrenals, and kidneys. The VHL tumor suppressor gene on chromosome 3p26-25 is partially or completely deleted in 20 to 30% of families with VHL. We identified deletions ranging from 0.5 kb to 250 kb affecting part of or the entire VHL and flanking genes in 54 families. In 33 of the index patients, the breakpoints were precisely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
3
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 60 publications
(75 reference statements)
7
92
3
9
Order By: Relevance
“…Germline VHL mutations are heterogeneous but the largest group, accounting for about 30-40% of cases, consists of deletions (ranging from 0.5 to 250 kb) that remove one or more VHL exons and usually arise from Alu-mediated recombination. 45 The remaining mutations fall into two groups, missense substitutions and mutations predicted to cause truncated protein (nonsense, indels, splice site). In non-mosaic patients with classical VHL disease mutation detection is 495%.…”
Section: Molecular Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Germline VHL mutations are heterogeneous but the largest group, accounting for about 30-40% of cases, consists of deletions (ranging from 0.5 to 250 kb) that remove one or more VHL exons and usually arise from Alu-mediated recombination. 45 The remaining mutations fall into two groups, missense substitutions and mutations predicted to cause truncated protein (nonsense, indels, splice site). In non-mosaic patients with classical VHL disease mutation detection is 495%.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…However a subgroup of patients with a contiguous deletion of all or part of VHL and the HSPC300 gene develop retinal and CNS haemangioblastomas but have a low risk of RCC (sometimes called Type 1B phenotype). [45][46][47] Kindreds with phaeochromocytoma are designated as Type 2 VHL disease and usually have a germline missense mutation. Most such families are further characterised as Type 2B and manifest haemangioblastomas, RCC and phaeochromocytoma but Type 2A families manifest haemangioblastomas and phaeochromocytoma with a lower risk of RCC.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…Some have found that VHL deletions extending to include the actin-regulator gene HSPC300 appear to lower the risk of RCC and retinal angiomas development [Franke et al, 2009;Maranchie et al, 2004]. Nonsense and frameshift mutations have a higher age-related risk for RCC and hemangioblastomas than missense mutations thought to interfere with pVHL's structural integrity [Ong et al, 2007].…”
Section: Renal Cell Carcinoma Associated With Vhl Diseasementioning
confidence: 99%
“…53 Alu mediated recombination is one of the major cause for genome instability and chromosome translocation, underlining various diseases 54,55 and malignancy. [56][57][58] Closely related to recombination, Alus are (as with other TEs) sites prone to DNA damage. Alus are recently found enriched in chromosome common fragile sites, 59 which tend to break, although they are part of normal chromosome structure and play an important function in sister chromatid exchange and other recombinatory functions.…”
Section: Being a Large Part Of The Genome Alus In Cis Directly Contrmentioning
confidence: 99%